Analysis of the Influence of Financial Ratios and Macroeconomic on Stock Prices of Transportation and Logistics Sector Companies Listed on the Indonesia Stock Exchange (IDX) - Wahyuningtiyas, Linda; Taufiq, M; Utami, Anisa Fitria (Trunojoyo University of Madura, 2024)
The purpose of this study is to examine the effects of financial ratios and macroeconomic factors on the stock prices of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach is employed in the research, utilizing secondary data from the IDX website and the official websites of 12 companies. The study applies purposive sampling and analyzes the data using panel data regression with E-Views 12. The results indicate that ROE, Interest Rate, and Firm Value have a partial effect on stock prices, while the Current Ratio does not significantly impact stock prices. Additionally, all independent variables have a significant simultaneous effect on stock prices.